Distribusi Upah Terhadap Produktivitas Kerja dan Kerja Sama dalam Ekonomi Islam - Maulana, Rivan; Verawati, Heni; Sisdianto, Ersi (Jurnal Akuntansi, Keuangan, dan Manajemen, 2025)
Purpose: This study examines the influence of work experience, productivity, and collaborative work on wage dispersion from an Islamic economic perspective, with a focus on Andalas Surya Gemilang Mini Plant workers. This study evaluates how these factors affect wage dispersion and provides insights into the principles of Islamic economics. Methodology: A descriptive quantitative approach was used, involving 109 workers from the Mini Plant Andalas Surya Gemilang. Data were collected through questionnaires and analyzed using SmartPLS 3 for structural equation modelling. The hypotheses were tested using regression analysis to evaluate the influence of work experience, productivity, and collaborative work on wage dispersion. Results: This study found that Work experience and collaborative work had no significant effect on wage dispersion, while productivity had a significant effect. The combination of these three factors significantly contributes to wage dispersion. Conclusions: This study found that productivity significantly affects wage dispersion at Mini Plant Andalas Surya Gemilang, whereas work experience and collaboration have fewer direct effects. Combining these factors contributes to the wage gap. Limitations: This research is limited to one organization, the Andalas Surya Gemilang Mini Plant, which may limit the generalization of the results to other industries. Future research could expand this scope to other sectors for greater insight. Contributions: This study provides practical recommendations for companies to consider work experience and productivity in designing compensation systems that motivate employees and encourage collaboration, in line with Islamic values that emphasize justice and welfare.